2020
DOI: 10.1186/s41073-019-0089-z
|View full text |Cite
|
Sign up to set email alerts
|

The acceptability of using a lottery to allocate research funding: a survey of applicants

Abstract: Background: The Health Research Council of New Zealand is the first major government funding agency to use a lottery to allocate research funding for their Explorer Grant scheme. This is a somewhat controversial approach because, despite the documented problems of peer review, many researchers believe that funding should be allocated solely using peer review, and peer review is used almost ubiquitously by funding agencies around the world. Given the rarity of alternative funding schemes, there is interest in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 25 publications
(25 reference statements)
0
38
0
2
Order By: Relevance
“…Of note, panels applied the random selection only in a few cases, in 8 (6.0%) of 134 applications. In the context of the Explorer Grant scheme of the HRC-NZ, Liu et al 28 recently reported that most applicants agreed with the use of a random selection. In this study, the SNSF received a few unsolicited questions about the procedure but otherwise no negative or positive reactions to the use of random selection were received from applicants.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, panels applied the random selection only in a few cases, in 8 (6.0%) of 134 applications. In the context of the Explorer Grant scheme of the HRC-NZ, Liu et al 28 recently reported that most applicants agreed with the use of a random selection. In this study, the SNSF received a few unsolicited questions about the procedure but otherwise no negative or positive reactions to the use of random selection were received from applicants.…”
Section: Discussionmentioning
confidence: 99%
“…Short proposals are screened for eligibility and then funded at random until the budget is exhausted. A recent study reported that those who were funded by the lottery supported this system, however, it did not evaluate the impact of receiving funding on scientific output (Liu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the Explorer Grant scheme of the HRC-NZ, Liu et. al [28] recently reported that most applicants agreed with the use of a random selection. In this study, no negative or positive reactions to the use of random selection were received from applicants.…”
Section: Discussionmentioning
confidence: 99%